2015
DOI: 10.1111/jai.12947
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes of fish assemblages associated with artificial reefs off the northern coast of Rio de Janeiro, Brazil

Abstract: Summary Changes in fish assemblages associated with artificial reefs 5‐km offshore (Southeast Brazil) were assessed. Bottom gillnets were used for 1 month per year for up to 15 years after the artificial reef had been established. Totals of 552 fishes were caught, with Chloroscombrus chrysurus and Conodon nobilis the dominant species and Scianidae the richest family. Species richness, abundance and biomass varied significantly with time, increasing gradually for several years but decreasing thereafter. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…The contrasted patterns detected for benthic and pelagic piscivores also demonstrated that species diet must to be considered together with their habitat preferences. This can explain why ambiguous patterns were identified in other AR systems when piscivorous species were pooled (Neves dos Santos and Zalmon, 2015). Similarly, because species with significant responses to AR deployment are mainly sedentary with narrow distributional range, we should ask if the use of…”
Section: A Functional Traits-based Monitoring Of Arsmentioning
confidence: 99%
“…The contrasted patterns detected for benthic and pelagic piscivores also demonstrated that species diet must to be considered together with their habitat preferences. This can explain why ambiguous patterns were identified in other AR systems when piscivorous species were pooled (Neves dos Santos and Zalmon, 2015). Similarly, because species with significant responses to AR deployment are mainly sedentary with narrow distributional range, we should ask if the use of…”
Section: A Functional Traits-based Monitoring Of Arsmentioning
confidence: 99%
“…2015). In many cases, researchers have had to take targeted gear approaches to sample a subset of the fishery associated with these structures (Neves dos Santos and Zalmon 2015; Bollinger and Kline 2017; Streich et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Four different reef types were sampled in this study: (1) concrete rubble consisting of fragmented concrete, (2) limestone reefs comprising piles of limestone fragments/chunks, (3) human-made shell reefs consisting of oyster shells, and (4) oil and gas reefs consisting of metal supports from derelict structures. Each paired control site was located 500 m adjacent to its paired reef following the recommendation of Neves dos Santos and Zalmon (2015), who analyzed fish communities near artificial reefs to determine the relationship between distance (0-300 m) from the reef and species richness and abundance. They noted significant differences (lower abundances and lower species richness) in fish communities located 50-300 m from the reefs.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the use of ARs as fishery production site (Leitão, 2013;Rouse et al, 2018) and the increasing knowledge about the design of artificial habitats (Bortone et al, 2000;Kim et al, 2016;Smith et al, 2016), many issues regarding the performance and fishing capacity of ARs remain poorly understood. These issues are even less studied in coastal zones near estuarine systems, especially in tropical seas, despite the worldwide ecological and economic importance of estuaries and the potential of ARs for enhancing fishery resources (Folpp et al, 2013;Lowry et al, 2014;Santos and Zalmon, 2015;Becker et al, 2017;Taylor et al, 2018). Some community descriptors, such as fish abundance, species richness biomass and diversity, are often used as predictors of fishing productivity related to artificial structures (Rouse et al, 2018;Streich et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since intra-annual changes in the composition and structure of fish assemblages are common, surveys conducted for the long-term assessment of ARs should cover different seasons, especially in tropical estuarine areas, wherein environmental disturbances influence fish attraction (Santos and Zalmon, 2015). Surprisingly few studies have addressed the seasonal changes in fish attraction over extended periods (Ribeiro et al, 2008;Lowry et al, 2014;LeClair et al, 2016;Becker et al, 2017;Taylor et al, 2018), considering that the spatial and temporal associations of fish from sites enhanced with artificial structures versus reference sites is crucial to understand how ARs can be integrated within a broader local fisheries plan (Becker et al, 2018;Lima et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%